Loop-check elimination for non-transitive distributed knowledge logic - Pliuškevičienė, Aida (Lietuvos matematikos rinkinys, 2008)
A non-transitive distributed knowledge logic TnD, obtained from multi-modal logic Tn by adding distributed knowledge operator, is considered. Sound and complete loop-check-free sequent calculus for this logic is proposed. Termination of derivations in proposed calculus is justified.
Keywords: logic of knowledge; distributed knowledge; sequent calculus; loop-check